2002
DOI: 10.4049/jimmunol.169.12.6822
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Repertoire Development in Fetal and Neonatal Piglets. VIII. Colonization Is Required for Newborn Piglets to Make Serum Antibodies to T-Dependent and Type 2 T-Independent Antigens

Abstract: Cesarean-derived piglets were reared for 5 wk under germfree conditions or monoassociated with a benign Escherichia coli (G58-1) or a enterohemorrhagic strain (933D) derived from O157:H7, and immunized i.p. with the T-dependent (TD) Ags fluorescein-labeled (FL) keyhole limpet hemocyanin or trinitrophenylated (TNP) keyhole limpet hemocyanin and the type 2 T-independent Ags TNP-Ficoll or FL-Ficoll. Only colonized piglets showed an increase in serum IgG, IgA, and IgM and had serum Abs to FL, TNP, and colonizing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 60 publications
7
105
0
1
Order By: Relevance
“…In conventional piglets or in piglets specifically colonised with flora, V-segment usage in the intestinal mucosa expands, indicating that microbial colonisation drives expansion of repertoire, as well as compartments. Consistent with this, germ-free pigs mount poor specific systemic antibody responses [13], unless colonised with commensal flora. Even mono-association with a single commensal appears to be able to promote both a specific and a polyclonal expansion of IgM, IgG and IgA secreting lymphocytes in the mesenteric lymph nodes, spleen and Peyer's patches [16].…”
Section: Environmental Effects On Early Immune Developmentsupporting
confidence: 58%
“…In conventional piglets or in piglets specifically colonised with flora, V-segment usage in the intestinal mucosa expands, indicating that microbial colonisation drives expansion of repertoire, as well as compartments. Consistent with this, germ-free pigs mount poor specific systemic antibody responses [13], unless colonised with commensal flora. Even mono-association with a single commensal appears to be able to promote both a specific and a polyclonal expansion of IgM, IgG and IgA secreting lymphocytes in the mesenteric lymph nodes, spleen and Peyer's patches [16].…”
Section: Environmental Effects On Early Immune Developmentsupporting
confidence: 58%
“…In piglets maintained germ-free (GF), the length of the IPP actually increases, suggesting that without environmental stimuli, their possible status as a primary B cell organ may continue (12). In conventional or colonized piglets IgA production becomes dominant (21). The observation that hindgut lymphoid tissues change their function during postnatal development has also been reported in rabbits (22).…”
mentioning
confidence: 96%
“…All studies were approved by the Animal Care and Use Committee of the NADC (Ames, IA). Most animals remained germfree whereas others were colonized with benign Escherichia coli as described previously (52), although we previously showed that E. coli colonization did not affect our results (12). Groups of three to five piglets from the same litter were used and were treated one of three ways: 1) inoculated intranasally with 10 4 TCID 50 PRRSV; 2) inoculated intranasally with 10 4 TCID 50 SIV; or 3) given a sham inoculum.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The BAL cell pellet was suspended in TRIzol and frozen at Ϫ20°C. Blood collected in anticoagulation tubes was processed as previously described for the recovery of PBMC and plasma (12,52,53). The plasma was used for Ig determinations and was cultured for virus as described previously (54).…”
Section: Sample Collectionmentioning
confidence: 99%